Netporn: DIY Web Culture and Sexual Politics - Jacobs, Katrien (Rowman & Littlefield Publishers, 2007)
Netporn delves into the aesthetics and politics of sexuality in the era of do-it-yourself (DIY) Internet pornography. Katrien Jacobs, drawing on digital media theory and interviews with Web porn producers and consumers, offers an unprecedented critical analysis of Web culture as digital artistry and of the corresponding heightened government surveillance and censorship of the Internet. Netporn features Web users who question the goals of global commercial porn industries-whether they are engaged in Usenet fringes, video blogging, peer-to-peer distribution, porn art collectives, or decadent amateurism. Emphasizing gender and cultural differences, Jacobs shows how the creative uses of netporn images and services are important ways of exploring or redefining the 'network body' and indispensable ingredients of a maturing network society.